Biological Variability of Sweat Gland Pores in the Fingerprints of a Fars Iranian Family from Khorasan Razavi Province, Iran - Mariam Tafazoli; Nasser Mahdavi Shahri; Hamid Ejtehadi; Farhang Haddad; Hadi Jabbari Nooghabi; Mehrnoosh Mahdavi Shahri; Somayeh Naderi (Negah Institute for Scientific Communication, 2013)
Introduction: Poroscopy is a method of identification in which the characteristics of sweat pores are compared from different aspects. These pore openings are present along the friction ridges found on the distal end of digits, palms and soles in the hands and feet. Materials amd Methods: This study enrolled 100 Iranian males from the Fars family who resided in Khorasan Razavi Province. The average age of participants was 20 years. Pictures of their finger tips and tri-linear A positions of both hands were taken using a Dino-Lite-313 puls and Dino-capture software. Then circle areas of 80l16-5l12 mm2 were considered in all pictures and the numbers of pore ducts of the sweat glands that occurred in these given areas were counted. The results were analyzed by Minitab Statistical Software. The finger and palm printing method was used in order to complete the sampling process. The size, number, position and relative distance of the pores on the fingers and toes were examined in detail. Results: Evaluation of the qualitative results and comparison with the findings of other studies showed morphological variety within the sweat pores of the Fars family of the Iranian population. Conclusion: The variance in morphology and density of these pore canals can probably represent a foundation for classifying humans or applying the same in biological anthropology.